2005
DOI: 10.1111/j.1398-9995.2005.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic bronchopulmonary aspergillosis

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) occurs in nonimmunocompromised patients and belongs to the hypersensitivity disorders induced by Aspergillus. Genetic factors and activation of bronchial epithelial cells in asthma or cystic fibrosis are responsible for the development of a CD4+Th2 lymphocyte activation and IgE, IgG and IgA‐AF antibodies production. The diagnosis of ABPA is based on the presence of a combination of clinical, biological and radiological criteria. The severity of the disease is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(71 citation statements)
references
References 86 publications
(104 reference statements)
0
65
0
6
Order By: Relevance
“…Other authors (11) have reported that rAspf3 and rAspf4 allow discrimination between ABPA and non-ABPA patients with atopic A. fumigatus-positive skin tests. According to the data in the literature (2,11,21), rAspf4 (a cytoplasmic protein with unknown function) and rAspf6 recombinants have provided powerful tools for the accurate diagnosis of ABPA. Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors (11) have reported that rAspf3 and rAspf4 allow discrimination between ABPA and non-ABPA patients with atopic A. fumigatus-positive skin tests. According to the data in the literature (2,11,21), rAspf4 (a cytoplasmic protein with unknown function) and rAspf6 recombinants have provided powerful tools for the accurate diagnosis of ABPA. Kraemer et al (13) have shown that allergen-specific IgE against these two recombinants could be detected almost exclusively in the sera of patients with ABPA.…”
Section: Discussionmentioning
confidence: 99%
“…Minor diagnostic criteria include repeated detection of Aspergillus species in sputum samples, a history of expectoration of brown plugs or flecks, and late skin reactivity to Aspergillus antigens. Despite these criteria, diagnosis of ABPA in cystic fibrosis patients remains particularly difficult (3,16,21,22). Therefore, as stated in the most recent consensus document on the diagnosis and therapy of ABPA in cystic fibrosis patients (19), serological findings should strongly contribute to the confirmation or exclusion of clinically suspected ABPA.…”
mentioning
confidence: 99%
“…Aberrant immune responses to A. fumigatus result in a spectrum of human diseases that include allergic bronchopulmonary aspergillosis. In severe cases, this leads to pulmonary hypersensitivity and compromised lung function, which is called farmer's lung (26). A mild form of infection is the colonization of cavities within the lung, known as aspergilloma or a fungal ball, and is often found in immunocompetent people who have recovered from a Mycobacterium tuberculosis infection (14).…”
mentioning
confidence: 99%
“…It can cause allergic bronchopulmonary aspergillosis, pulmonary aspergilloma and invasive aspergillosis. In the latter the symptoms can be cough, fever, lowgrade chest pain, dyspnea and hemoptysis (2) while in allergic bronchopulmonary aspergillosis malaise, fever, presence of sputum plugs and purulent sputum, cough, chest pain, and hemoptysis can be observed beside the symptoms of asthma (23). The pulmonary aspergilloma can cause hemoptysis or it can be without symptoms.…”
Section: Introductionmentioning
confidence: 99%